Terapia familiar: retos y reflexiones - Zevallos, Roxana (2000)
This article is based on 10 years of experience in training and working with families and couples in Lima. Trainees usually come up with interesting inquiries that had helped us co-constructed our training program as well as re-framed our therapeutic practice. The challenges and possibilities proposed by a challenging and sometimes compelling context has helped us in developing some reflexions we want to share through this article.